2017
DOI: 10.1093/biolinnean/blw035
|View full text |Cite
|
Sign up to set email alerts
|

Egg spotting pattern in common cuckoos and their great reed warbler hosts: a century perspective

Abstract: The characteristics of common cuckoo (Cuculus canorus) and host eggs are widely thought to 24 have coevolved over time, but few studies have tested this prediction. We compared cuckoo 25 eggs with those of its primary host, the great reed warbler (Acrocephalus arundinaceus) from 26 four time periods spanning >100 years (between 1900 and 2014), and studied if cuckoo 27 eggshell patterns better resembled those of their hosts over time. We used image analysis to 28 compare five eggshell pattern variables, relatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 62 publications
0
6
0
Order By: Relevance
“…Another reason that may help explain this pattern is the general difficulty of comprehensively monitoring the nests of bird populations in the field, hence studying one‐to‐one systems where nests of only one species of host need to be monitored has likely shaped their prevalence in the literature. While difficult to quantify, this is particularly evident for studies involving the detailed examination of the same host populations over multiple years, such as the Common Reed‐warblers ( Acrocephalus scirpaceus ) at Wicken Fen in the United Kingdom (Davies, 2000; Stoddard & Kilner, 2013) or the Great Reed‐warblers ( A. arundinaceus ) near Apaj village in Hungary (Geltsch et al, 2017; Hauber et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Another reason that may help explain this pattern is the general difficulty of comprehensively monitoring the nests of bird populations in the field, hence studying one‐to‐one systems where nests of only one species of host need to be monitored has likely shaped their prevalence in the literature. While difficult to quantify, this is particularly evident for studies involving the detailed examination of the same host populations over multiple years, such as the Common Reed‐warblers ( Acrocephalus scirpaceus ) at Wicken Fen in the United Kingdom (Davies, 2000; Stoddard & Kilner, 2013) or the Great Reed‐warblers ( A. arundinaceus ) near Apaj village in Hungary (Geltsch et al, 2017; Hauber et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Male common cuckoos are known to vocalize using other, including aberrant forms of calls (Møller et al 2016), but these are observed and reported rarely. Here, we studied the "cukee" call, which occurs in our population at low but consistent frequencies in almost each year of our research during the past 20+ years (Geltsch et al 2017), whereas it is present in only two of a total of 1152 of common cuckoo recordings in the Xeno-Canto data base (also see above).…”
Section: Number Of Male Cuckoosmentioning
confidence: 99%
“…During our long-term research on common cuckoos (Geltsch et al 2017), we discovered a handful of individuals uttering both normal ("cu-coo") and aberrant ("cu-kee") calls ( Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, if, as it is common in terrestrial environments, conditions change from 1 year to another, the role of intra-clutch variation in egg rejection might differ between breeding seasons and for the different aspects of the egg's phenotype. So far, very few studies have addressed changes in eggshell color or spottiness in time (Geltsch et al, 2017) in the context of the coevolution of host and parasite eggs.…”
Section: Introductionmentioning
confidence: 99%